2007
DOI: 10.1002/jbm.a.31340
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine doping into diamond‐like carbon coatings inhibits protein adsorption and platelet activation

Abstract: The first major event when a medical device comes in contact with blood is the adsorption of plasma proteins. Protein adsorption on the material surface leads to the activation of the blood coagulation cascade and the inflammatory process, which impair the lifetime of the material. Various efforts have been made to minimize protein adsorption and platelet adhesion. Recently, diamond-like carbon (DLC) has received much attention because of their antithrombogenicity. We recently reported that coating silicon sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 120 publications
(206 reference statements)
2
60
1
Order By: Relevance
“…However, in the present work, the surface roughness increased with increasing contact angle (smaller surface energy). Hasebe, et al and Yu, et al reported that the surface roughness and microstructure have a negligible influence on the surface energy [23,28], with increasing fluorine content, which is due to changes which is consistent with the present results.…”
Section: Hemolysis Testsupporting
confidence: 92%
See 2 more Smart Citations
“…However, in the present work, the surface roughness increased with increasing contact angle (smaller surface energy). Hasebe, et al and Yu, et al reported that the surface roughness and microstructure have a negligible influence on the surface energy [23,28], with increasing fluorine content, which is due to changes which is consistent with the present results.…”
Section: Hemolysis Testsupporting
confidence: 92%
“…a-C:H films have also shown promising results in hemocompatible coating technology. To date many types of a-C:H films have been applied to medical devices [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that an a-C:H:F film with sufficient C-F bonds on its surface showed excellent antithrombotic properties owing to its hydrophobicity. (16,17) This spectrum led us to expect the improvement of antithrombotic properties, because it is characteristic of an antithrombotic a-C:H:F film.…”
Section: Discussionmentioning
confidence: 99%
“…(14,15) We previously showed that fluorine doping in a-C:H films contributes to a reduction of blood cell adhesion and adsorption of plasma protein. (16,17) We also reported that a-C:H:F-coated biomaterials can play a nontoxic mediating role in vivo, (18) and we developed fluorine-incorporated a-C:H (a-C:H:F) coating techniques for vascular interventional devices using radio frequency plasma-enhanced chemical vapor deposition (RF-PECVD). (19) However, the adhesion of leukocytes in relation to a-C:H:F has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%